Twice- or Once-Daily Dosing of Direct Oral Anticoagulants, a systematic review and meta-analysis. Issue 197 (January 2021) - Mainbourg, S.; Cucherat, M.; Provencher, S.; Bertoletti, L.; Nony, P.; Gueyffier, F.; Mismetti, P.; Grange, C.; Durieu, I.; Kilo, R.; Laporte, S.; Grenet, G.; et al.
Abstract: Aim: The direct oral anticoagulants (DOAC) have similar half-lives, but the dosing regimen varies between once daily (QD) or twice daily (BID). For some prescribers, the QD regimen improves compliance. Others prefer BID regimens to promote better stability of plasma concentrations, particularly in the event of missed doses. Limited level of evidence provides guidance about the best treatment strategy. The purpose of this study was to compare the treatment effect of QD vs. BID administration of DOACs in major orthopedic surgery (MOS), non-valvular atrial fibrillation (NVAF), venous thromboembolism (VTE), and acute coronary syndrome (ACS). Methods: We conducted a systematic review up to April 2020. We included phase II clinical trials comparing DOAC QD vs BID with same daily dose. We extracted data for the occurrence of major thrombosis (proximal deep vein thrombosis, pulmonary embolism, myocardial infarction, ischemic stroke) and major hemorrhage (ISTH criteria and recommendations of the European Medicines Agency for surgical patients). Relative risks (RR) were combined using a fixed and random effects weighted meta-analysis. Results: Twelve randomized, controlled, phase II trials were included (10, 716 patients), representing 24 dosing regimen comparisons of apixaban, darexaban, edoxaban, rivaroxaban, letaxaban, and dabigatran. There was no difference for major thrombotic event (RRBID/QD = 1.06, 95%IC 0.86–1.30) nor for major bleeding (RRBID/QD = 1.02, 95%IC 0.84–1.23) between the BID vs QD regimens, without heterogeneity (I 2 = 0%). Conclusion: Our study does not support a global difference in term of efficacy and safety of the BID and QD regimens of DOAC in MOS, NVAF, VTE and ACS. Highlights: The dosing regimen of direct oral anticoagulants varies between once or twice daily according to molecule and indication chosen. We compare the risk of thrombosis and major bleeding from head to head phase II RCTs totalizing more than 10, 000 patients. Once or twice daily DOAC dosing regimens are associated with similar risk of thrombosis and major bleeding events